Endovascular Treatment of Ruptured Intracranial Aneurysms - Mirza Khinikadze; Vladimer Tsikarishvili; Koka Gogichashvili (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
Ruptured intracranial aneurysm is an immediate diagnostic and therapeutic condition. Coil occlusion is the first-line therapies for ruptured aneurysms and it should also be used to prevent re-rupture, which could result in severe brain damage. This is the treatment of choice for the majority of aneurysms. During coil treatment, the risk of intraoperative thromboembolic and hemorrhagic complications is extremely low. Endovascular coil treatment is thus a safe and effective method for preventing both short and long-term haemorrhage. Early recanalization of cases with neuro-visualization results in short and long-term haemorrhage. Aneurysm rupture is a life-threatening clinical condition that requires immediate diagnosis and treatment. Operative intervention should be performed as soon as possible to prevent aneurysm re-rupture. The recommended time interval after aneurysm rupture is 72 hours, and if possible, 24 hours. Endovascular coiling of ruptured aneurysms is a first-line remedy that rely on the angioarchitecture and location of the aneurysm. The primary endovascular treatment technique is coil occlusion with or without remodelling balloon assistance. In general, only aneurysms with coils are associated with relatively high rates of recanalization during acute periods, so further analysis and possible surgical treatment are advised.